Samuel Daniel et les traductions anglaises du Pastor Fido au XVIIe siècle en Angleterre : du voyage d’Italie à la naturalisation - Christine Sukic (Etudes Epistémè)
Samuel Daniel is often considered an imitator, especially of the Italian pastorals of Guarini and Tasso. In the sonnet he prefixed to the 1602 English translation of Guarini’s Pastor Fido, as well as in his other works, he asserted that translation was the first step towards the formation of a national literature in the English language. It was thus necessary for English poets to assimilate the Italian model, through translation, imitation, and finally creation.